Reduction of Fructosamine Levels after Ramadan Fasting in Children with Type 1 Diabetes Mellitus - Faizi, Muhammad; Rochmah, Nur; Marcos, Imella; Endaryanto, Anang; Soetjipto, Soetjipto (Indonesian Journal of Medicine, 2022)
Background: Ramadan fasting is one religious challenge for children with type 1 diabetes mellitus (T1DM) which required specific management and strict monitoring. Fructosamine, which reflects glycemic control within 2-3 weeks, is an ideal parameter of glycemic control in Ramadan fasting. This study aimed to analyzed the effect of Ramadan fasting on fructosamine level of children with T1DM.Subjects and Method: This prospective cohort study included children aged under 18 years old diagnosed wit T1DM for >6 months at Dr. Soetomo Hospital, Surabaya, Indonesia in Ramadan 1438 H (May-June 2017). The independent variable from this study was Ramadhan fasting and the dependent variables were fructosamine and HbA1c. The sampling technique was total sampling. Forty-two children were included and devided into 27 children in the fasting and 15 children in the non-fasting group. Fructosamine and HbA1c levels were measured before, mid- and after Ramadan and the comparison between groups were analyzed using the independent T-test.Results: The mean age of all the subjects was 8.95 (SD=3.2) years old, 47.6% were males. The mean (SD) HbA1c level of all the subjects was 10.42 (1.16) %. There was a mild reduction of mean fructosamine level after Ramadan in the fasting group. There was no significat differece I fructsamie level before (Mean= 556.8; SD= 180.39; p= 0.620), mid (Mean= 568.07; SD= 175.37; p= 0.520), and after Ramadhan between groups (Mean= 539.41; SD= 173.04; p= 0.410) respectively. The average fructosamine levels after Ramadan was positively and strongly related to HbA1c (r=0.69; p<0.001). There was no case of severe hypoglycemia and diabetic ketoacidosis in both groups.Conclusion: There is a reduction of mean fructosamine level after Ramadan fasting in children with T1DM although it isn’t statistically significant.Keywords: type 1 diabetes, children, fasting, Ramadan, fructosamineCorrespondence: Nur Rochmah. Department of Child Health, Dr. Soetomo General Hospital/ Faculty of Medicine, Universitas Airlangga. Mayjend Prof. Dr. Moestopo No. 6-8, Surabaya, East Java, Indonesia, 60286. Number: +6281703501118. Email: drnurrochmah@gmail.com.Indonesian Journal of Medicine (2022), 07(02): 131-137https://doi.org/10.26911/theijmed.2022.07.02.02